2021
DOI: 10.3390/foods10020387
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Use of Low and No-Calorie Sweeteners in Non-Alcoholic Beverages in Slovenia

Abstract: Excessive sugar intake and the associated increased obesity risk indicate that food reformulation is needed. Non-alcoholic beverages are often high in free sugars, making reformulation with low and no-calorie sweeteners (LNCS) a common choice. Our knowledge of the use of LNCS in the European food supply is, however, very limited. This study aimed to evaluate the trends in the use of LNCS in different non-alcoholic beverages in the Slovenian food supply over the course of two years. We assessed which LNCS are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
3
17
0
1
Order By: Relevance
“…An international review found similar predominant categories i.e., beverages (soft drinks and juices) as the major source of NNS followed by dairy products, confectionery, and table-top sweeteners (included in our Special Foods category) [ 33 ]. Rising use of NNS in non-alcoholic drinks in our study was also reported in a recent study in Slovenia where the use of low and no-calorie sweeteners increased from 13.2% to 15.5% over a two year period (2017 and 2019) [ 34 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…An international review found similar predominant categories i.e., beverages (soft drinks and juices) as the major source of NNS followed by dairy products, confectionery, and table-top sweeteners (included in our Special Foods category) [ 33 ]. Rising use of NNS in non-alcoholic drinks in our study was also reported in a recent study in Slovenia where the use of low and no-calorie sweeteners increased from 13.2% to 15.5% over a two year period (2017 and 2019) [ 34 ].…”
Section: Discussionsupporting
confidence: 87%
“…The food industry is responding to consumer demand for lower-sugar products with greater use of NNS; however, the industry should be encouraged to develop new products with lower sugar content and reformulate existing products using the successful sodium reduction model [ 37 ] by gradually reducing sugar levels over time to improve the consumer’s acceptance of lower sugar, less sweet products [ 34 ]. The UK government-led sodium reduction program uses timebound voluntary sodium reduction targets for over 80 processed food categories, which are lowered progressively over time, to prompt food product reformulation and allow time for consumers to adjust to any flavor changes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Out of all foods and drinks, non-alcoholic beverages have been shown to be one of the major contributors to LNCS availability (15) and intake (24,25). In Slovenia, monitoring of the use of LNCS in non-alcoholic beverages was undertaken for products available in 2017, following by further data collection in 2019 (26). While no significant differences were observed in a comparative study (26), signs of increased use of LNCS were found, making this area very interesting for further research.…”
Section: Introductionmentioning
confidence: 99%
“…In Slovenia, monitoring of the use of LNCS in non-alcoholic beverages was undertaken for products available in 2017, following by further data collection in 2019 (26). While no significant differences were observed in a comparative study (26), signs of increased use of LNCS were found, making this area very interesting for further research. In Slovenia, there are currently no legislative restrictions or taxations for the content of sugars in sugary drinks.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of sugars with artificial sweeteners is also often used as a strategy for reducing dietary sugar intake. Studies in Europe [66,67] and in Hong Kong [68] have found that the use of low calorie and artificial sweeteners is increasingly more common, whereby manufacturers utilize them to achieve a lower sugar content in their products without affecting taste. The potential health effects of this increased prevalence of low calorie and artificial sweetener use in the population's diet is largely unknown.…”
Section: Discussionmentioning
confidence: 99%